PENGARUH SOCIAL MEDIA MARKETING MELALUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN SAYUR ORGANIK DI WARUNG 1000 KEBUN BANDUNG - Dinda Selvia; Yosini Deliana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The number of social media users could be an opportunity to be used as a means of social media marketing for businesses in promoting their products. Warung 1000 Kebun is one of the online stores in Bandung that uses marketing through social media specifically Instagram. This raises the problem of whether choosing Instagram as social media marketing by Warung 1000 Kebun is effective and received a good response from Instagram users, especially followers of Warung 1000 Kebun in purchasing organic vegetable products. In this study, the effectiveness of social media marketing was measured using four social media marketing indicators according to Chris Heuer in Solis (2010), namely context, communication, collaboration, and connection on purchasing decisions of organic vegetables from Warung 1000 Kebun. This research uses a quantitative research design with survey methods. Sampling in this study uses a non-probability sampling technique and uses purposive sampling method with the number of samples set to as many as 100 people. A questionnaire with a Likert scale rating system of 1–5 was used to collect the data. Multiple linear regression carried out using SPSS 20 was the data analysis method.  The results showed that of the four social media marketing indicators, the connection indicator was the most influential followed by the context indicator which had a positive and significant impact on purchasing decisions for organic vegetables at Warung 1000 Kebun.